PENERAPAN MODEL COOPERATIVE LEARNING TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI PESERTA DIDIK PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Zaenul Slam (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
ABSTRACTNowadays, education is required to grow in accordance with the increasingly sophisticated era. Changes in the composition of high-level thinking skills in 21st Century skills as a consequence of changing demands for educational standards that require graduates who are critical, creative, communicative, and collaborative. The learning process that occurs in schools at the moment emphasizes more on Hard Skills and less emphasis on Soft Skills. This is due to the fact that in practice learning done in schools there are still many that run as is where the learning is still transferring knowledge from teachers to students, so to overcome these problems the Models of Cooperative Learning Type Student Teams Achievement Division (STAD) is applied in the learning process carried out by the teacher with the aim of developing aspects of Soft Skills especially in the communication skills of students. This study uses qualitative and quantitative approaches with classroom action research methods. The purpose of using classroom action research methods is to improve and improve the quality of the process and learning outcomes (students' communication skills). The stages in this study include the stages of planning, implementing actions, observations, and reflections. Data obtained in this study includes activity observation sheets the teacher, and the observation sheet of students 'activities.The results of observations of students' communication abilities in the first cycle of actions obtained enough categories (65.72%) and in the second cycle of actions experienced an increase that is obtained a good category (81.71%). It was concluded that by applying the models of Cooperative Learning Type STAD in Social Sciences learning can improve students' communication skills.Keywords: Cooperative Learning Type STAD, Soft Skills, Communication ABSTRAKDewasa ini pendidikan dituntut untuk terus berkembang sesuai dengan perkembangan zaman yang semakin canggih. Perubahan komposisi kemampuan berpikir tingkat tinggi pada keterampilan Abad 21 sebagai konsekuensi perubahan tuntutan-tuntutan standar-standar pendidikan yang menghendaki lulusan yang kritis, kreatif, komunikatif, dan kolaboratif. Proses pembelajaran yang terjadi di sekolah saat ini lebih menekankan kepada Hard Skills dan kurang menekankan kepada Soft Skills. Hal ini disebabkan karena dalam praktiknya pembelajaran yang dilakukan di sekolah masih banyak yang berjalan apa adanya yang mana pembelajarannya masih transfer pengetahuan dari guru kepada siswa, maka untuk mengatasi permasalahan tersebut diterapkan model Cooperative Learning Tipe Student Teams Achievement Division (STAD) dalam proses pembelajaran yang dilakukan oleh guru dengan tujuan untuk mengembangkan aspek Soft Skills khususnya dalam kemampuan komunikasi peserta didik. Penelitian ini menggunakan pendekatan kualitatif dan kuantitatif dengan metode penelitian tindakan kelas. Tujuan dari penggunaan metode penelitian tindakan kelas yaitu untuk memperbaiki dan meningkatkan mutu proses dan hasil pembelajaran (kemampuan komunikasi peserta didik). Adapun tahapan dalam penelitian ini meliputi tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data yang diperoleh dalam penelitian ini meliputi lembar observasi aktivitas guru, dan lembar observasi aktivitas peserta didik. Hasil observasi kemampuan komunikasi peserta didik pada tindakan siklus I diperoleh katagori cukup (65,72%) dan pada tindakan siklus II mengalami peningkatan yaitu diperoleh katagori baik (81,71%). Berdasarkan hasil observasi dapat disimpulkan bahwa dengan menerapkan model Cooperative Learning Tipe STAD pada pembelajaran Ilmu Pengetahuan Sosial dapat meningkatkan kemampuan komunikasi peserta didik.Kata Kunci: Cooperative Learning Tipe STAD, Soft Skills, Komunikasi